The contribution of indigenous multipurpose trees found in Southern Africa to increased livestock production and climate change adaptation: a review - Mpofu, Mellisa Chengetai; Makumbe, Peter; du Toit, Linde; Chikwanda, Denice; Madzimure, James; Chakeredza, Sebastian (Frontiers in Climate, 2025)
Feed shortages during the dry season remain a critical challenge for livestock production in Southern Africa, where ruminant farming supports livelihoods and food security. This review assesses the role of indigenous multipurpose trees (MPTs) in enhancing ruminant livestock production during the dry season and climate change adaptation. Using PRISMA 2020 guidelines, the review systematically analyzed 41 ethnobotanical studies and 19 in vivo trials, identifying key gaps in prior reviews regarding quantitative ethnobotanical metrics, regional coverage, and climate adaptation mechanisms. The review identified 122 plant species from 34 botanical families and 78 genera browsed by ruminants, with Dichrostachys cinerea and Colophospermum mopane emerging as the most frequently cited species. These MPTs provide essential ecosystem services, including medicine, food, construction materials, firewood, and ethnoveterinary uses, while also contributing to climate resilience through shade, windbreaks, and insect repellent properties. The findings demonstrate that integrating these trees into livestock diets improves body weight, milk and meat production, and reduces methane emissions. Despite their potential, invasive species like D. cinerea require careful management. We recommend adopting non-invasive, high-value species such as Acacia erioloba, Sclerocarya birrea, Boscia albitrunca, and C. mopane into silvopastoral systems to mitigate feed shortages and enhance climate resilience. Future efforts should focus on domestication, conservation, and policy support to optimize their use in sustainable livestock production.